Correlates of meeting the combined and independent aerobic and strength exercise guidelines in hematologic cancer survivors - James R. Vallerand; Ryan E. Rhodes; Gordon J. Walker; Kerry S. Courneya (International Journal of Behavioral Nutrition and Physical Activity, 2017)
Abstract Background Most previous research on the correlates of physical activity has examined the aerobic or strength exercise guidelines separately. Such an approach does not allow an examination of the correlates of meeting the combined guidelines versus a single guideline, or one guideline versus the other. Here, we report the prevalence and correlates of meeting the combined and independent exercise guidelines in hematologic cancer survivors (HCS). Methods In a population-based, cross-sectional survey of 606 HCS from Alberta, Canada using a mailed questionnaire, we obtained separate assessments of aerobic and strength exercise behaviors, as well as separate assessments for motivations, regulations, and reflective processes using the multi-process action control framework (M-PAC). Results Overall, 22% of HCS met the combined exercise guideline, 22% met aerobic-only, 10% met strength-only, and 46% met neither exercise guideline. HCS were more likely to meet the combined guideline over the aerobic-only guideline if they had no children living at home, and over both the aerobic and strength-only guidelines if they had completed university. As hypothesized, those meeting the combined guideline also had a more favorable strength-specific M-PAC profile (i.e., motivations, regulations, and reflective processes) than those meeting the aerobic-only guideline, and a more favorable aerobic-specific M-PAC profile than those meeting the strength-only guideline. Interestingly and unexpectedly, HCS meeting the combined guidelines also reported significantly greater aerobic-specific perceived control, planning, and obligation/regret than those meeting the aerobic-only guideline, and greater strength-specific perceived control, planning, and obligation/regret than those meeting the strength-only guideline. Conclusions Few HCS are meeting the combined exercise guidelines. M-PAC based variables are strong correlates of meeting the combined guidelines compared to aerobic or strength only guidelines. Strategies to help HCS meet the combined guidelines may need to promote more favorable behavioral regulations and reflective processes for both types of exercise rather than just the type of exercise in which HCS are deficient.